Blocking the effects of interleukin-6 in rheumatoid arthritis and other inflammatory rheumatic diseases: systematic literature review and meta-analysis informing a consensus statement - Schoels, Monika M (BMJ Publishing Group, 2013)
BACKGROUND: Suppression of the immunoinflammatory cascade by targeting interleukin 6 (IL-6) mediated effects constitutes a therapeutic option for chronic inflammatory diseases. Tocilizumab is the only IL-6 inhibitor (IL-6i) licensed for rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA), but also other agents targeting either IL-6 or its receptor are investigated in various indications. OBJECTIVE: To review published evidence on safety and efficacy of IL-6i in inflammatory diseases. METHODS: We performed systematic literature searches in Medline and Cochrane, screened EULAR and American College of Rheumatology meeting-abstracts, and accessed http://www.clinicaltrials.gov. RESULTS: Comprehensive evidence supports the efficacy of tocilizumab in RA in DMARD-naïve patients, and after DMARD- and TNFi-failure. Randomised comparisons demonstrate superiority of tocilizumab in JIA, but not ankylosing spondylitis (AS). Other indications are currently investigated. Additional IL-6i show similar efficacy; safety generally appears acceptable. CONCLUSIONS: IL-6i is effective and safe in RA and JIA, but not in AS. Preliminary results in other indications need substantiation.